2017
DOI: 10.1007/s13311-016-0497-4
|View full text |Cite
|
Sign up to set email alerts
|

Urate as a Marker of Risk and Progression of Neurodegenerative Disease

Abstract: Urate is a naturally occurring antioxidant whose levels are associated with reduced risk of developing Parkinson's disease (PD) and Alzheimer's disease. Urate levels are also associated with favorable progression in PD, amyotrophic lateral sclerosis, Huntington's disease, and multisystem atrophy. These epidemiological data are consistent with laboratory studies showing that urate exhibits neuroprotective effects by virtue of its antioxidant properties in several preclinical models. This body of evidence suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 57 publications
1
63
0
Order By: Relevance
“…From a mechanistic standpoint, uric acid is a peroxynitrite scavenger that is thought to mitigate the oxidative damage that contributes to the pathogenesis of MS [86] or PD [87]. In human subjects, serum levels of uric acid are inversely correlated with risk of PD [57][58][59], providing the rationale for clinical trials aimed at increasing urate levels. The Phase II study in Parkinson's disease revealed that oral inosine was safe and tolerated well by patients, even at doses of up to 3 grams per day [61].…”
Section: Inosine In Clinical Usementioning
confidence: 99%
“…From a mechanistic standpoint, uric acid is a peroxynitrite scavenger that is thought to mitigate the oxidative damage that contributes to the pathogenesis of MS [86] or PD [87]. In human subjects, serum levels of uric acid are inversely correlated with risk of PD [57][58][59], providing the rationale for clinical trials aimed at increasing urate levels. The Phase II study in Parkinson's disease revealed that oral inosine was safe and tolerated well by patients, even at doses of up to 3 grams per day [61].…”
Section: Inosine In Clinical Usementioning
confidence: 99%
“…Cell damage markers such as neurofilament in blood and cerebrospinal fluid may closely match other measures of disease progression, with reliability that may allow for a reduction in trial size in phase II trials. Blood urate, which increases in a large number of neurodegenerative diseases, may also be a marker for improved outcome; as urate has antioxidant properties, it is possible that urate levels may be a modifiable target for intervention as well [16]. In contrast, AD markers are being developed that reflect alterations of relevant pathways, and blood markers in MS hold the promise of being able to distinguish between inflammatory and neurodegenerative aspects of the disease.…”
mentioning
confidence: 99%
“…Since these early observations, accumulating epidemiological studies, laboratory data, preclinical models, and early clinical trial results have provided substantial support for a neuroprotective role for UA and its potential as a disease biomarker for PD (Constantinescu and Zetterberg, 2011;Chen et al, 2012;Crotty et al, 2017). In particular, UA has been suggested as a promising biomarker of reduced risk and milder progression in PD (Schlesinger and Schlesinger, 2008;Paganoni and Schwarzschild, 2017;Wen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%